The lasting impact of adolescence on left-right identification: Cohort replacement and intracohort change in associations with issue attitudes. (December 2016) - Rekker, Roderik
Abstract: This study examined how the ideological correlates of left-right identification in the Netherlands changed between 1980 and 2008, and whether these changes were driven by cohort replacement. Analyses on repeated cross-sectional data revealed an increasing association with immigration and a decreasing association with redistribution, secularism, and civil liberties. Cohort differences were found for cultural attitudes: Secularism was most important for voters who were adolescent between 1917 and 1960, while civil liberties were most important for the 1960–1980 cohort and immigration was relatively important for the 1980–2008 cohort. Consequently, over-time changes in the importance of cultural issues, but not redistribution, were partly driven by cohort replacement. This indicates that the left-right distinction is partly shaped by circumstances during voters' adolescent years. Highlights: The ideological meaning of left and right has changed between 1980 and 2008. This process is driven by both cohort replacement and intracohort change. Cohorts differ in the primacy of cultural, but not economic, issues. Circumstances during adolescence determine voters' interpretation of left and right.